PERSEPSI PETANI TERHADAP KINERJA DAN PROFITABILITAS USAHATANI JAGUNG HIBRIDA BIMA 2 BANTIMURUNG DI KABUPATEN GROBOGAN, PROVINSI JAWA TENGAH - Miyike Triana; Istriningsih ; (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2016)
ABSTRACT Farmer Perception towards Bima 2 Bantimurung Hybrid Corn Performance and its Farming Profitability in Grobogan District, Central Java Province. Indonesian Agency for Agricultural Research and Development (IAARD) committed to generate superior technologies easily adopted by users. One of the technologies is hybrid maize Bima 2 Bantimurung which has been released in 2007 and has been licensed by a company, namely PT Saprotan Benih Utama (PT SBU) in the same year. The variety has been produced, marketed and adopted by farmers. In order to evaluate the impact of adoption of IAARD innovation in the field, a study was conducted to analyze the farmers’ perception on the performance and profitability of hibrid maize Bima 2 Bantimurung. The study was conducted on May 2013 in Central Java Province by interviewing PT SBU, 60 farmers of respondents, and it was supported by secondary data that are relevant to the purpose of the study. Data were analyzed using descriptive method and farming system analysis. The results showed that the hybrid maize Bima 2 Bantimurung that has been marketed under the trademark of Pak Tani-2 was distributed in several provinces, but in terms of productivity it was less competitive than the product of competitors, namely hybrid maize P21 (R/C: 1.35 vs. 2.21). However, Bima 2 Bantimurung has been well adapted on marginal land and the forage can be used to feed animal. The adoption of Bima 2 Bantimurung by farmers was related to the marketing approach applied by the company, such as stock availability, ease of access to innovation, facilitation by the Technical Service of PT SBU, the bonus for the purchase of seeds and crops purchase guarantee. Based on feedback from users, the technology produced by IAARD should be continuously improved to increase its competitiveness and adoption by users. Keywords: hybrid maize, innovation, adoption, impactABSTRAKBadan Penelitian dan Pengembangan Pertanian (Balitbangtan) berkomitmen tinggi untuk menghasilkan teknologi-teknologi unggul yang mudah diadopsi pengguna. Salah satunya adalah jagung hibrida Bima 2 Bantimurung yang dilepas tahun 2007, dan telah dilisensikan kepada perusahaan pengganda yaitu PT. Saprotan Benih Utama (PT. SBU) pada tahun yang sama. Varietas tersebut telah diproduksi, dipasarkan dan diadopsi oleh petani. Dalam rangka mengevaluasi dampak dari adopsi inovasi Balitbangtan di lapangan, dilakukan kajian yang bertujuan untuk menganalisis persepsi petani terhadap kinerja dan profitabilitas usahatani jagung hibrida Bima 2 Bantimurung. Kajian dilakukan pada bulan Mei tahun 2013 di Provinsi Jawa Tengah dengan mewawancarai PT. SBU, 60 petani responden, serta ditunjang oleh data sekunder yang relevan dengan tujuan kajian. Data dianalisis dengan menggunakan metode deskriptif dan analisis usahatani. Hasil kajian menunjukkan bahwa jagung hibrida Bima 2 Bantimurung yang telah dipasarkan dengan merek dagang Pak Tani-2 telah tersebar di beberapa provinsi, namun masih kalah bersaing dengan produk kompetitor yaitu jagung P21 dari sisi produktivitas (R/C = 1,3 vs 2,2). Namun demikian, Bima 2 Bantimurung mampu beradaptasi di lahan marginal dan hijauannya dapat dimanfaatkan sebagai pakan ternak. Adopsi Bima 2 Bantimurung oleh petani dipengaruhi oleh pola pemasaran yang diterapkan perusahaan, seperti jaminan stok, kemudahan akses terhadap inovasi, pendampingan oleh Technical Service dari PT SBU, bonus untuk pembelian benih serta jaminan pembelian hasil panen. Berdasarkan umpan balik dari pengguna, teknologi yang dihasilkan oleh Balitbangtan tersebut perlu selalu diperbaiki dan disempurnakan untuk meningkatkan dayasaing dan adopsinya oleh pengguna. Kata kunci: jagung hibrida, inovasi, adopsi, dampak